SOLID PARTICLE CHARACTERIZATION. SOME ASPECT RELATED TO THE SHAPE EVALUATION BY USING SOFTWARE CORRELATIONS - EMILIAN-FLORIN MOSNEGUTU; VALENTIN NEDEFF; ALEXANDRA-DANA CHITIMUS; MARCIN JASIŃSKI; NARCIS BARSAN (Journal of Engineering Studies and Research, 2021)
This article presents a method for determining the Riley circularity evaluation, a characteristic that defines the shape of a solid particle. To determine this parameter, a working methodology was identified by using Mathcad. To verify this methodology 15 anthracite particles were inserted in the working file, the shape of which is different, to determine the analyzed characteristic.